Effectiveness of Corporate Social Responsibility Fund Distribution of PT. Jasa Marga in the Partnership and Community Development Program - Dedek Melisa; Marliyah Marliyah (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2022)
Financing or channeling is the giving of trust. This means that the achievement given really must be believed to be able to be returned by the recipient of the financing in accordance with the time and terms that have been mutually agreed upon. CSR (Corporate Social Responsibility) is a business commitment to act ethically, operate legally and contribute to improving the quality of life of employees and their families, local communities, and the wider community. The CSR concept involves an active and dynamic partnership between the government, companies and local communities. Micro, Small and Medium Enterprises as well as the Community Development Program, specifically for BUMN companies. This study aims for the author is to be able to determine the effectiveness of the Distribution of Corporate Social Responsibility Funds PT. Jasa Marga in the Partnership and Community Development Program. This study uses a qualitative method. The type of approach that the author uses is a type of qualitative descriptive analysis approach. The data used in this study is primary data. The population in this study is the Jasamarga Nusantara Tollroad Regional Devision as the person in charge of implementing the Jasamarga Nusantara Tollroad Regional Devision program for the Belmera Medan branch in 2020 and recipients of the Corporate Social Responsibility program, namely partnerships and recipients of environmental development assistance. The sample in this study is the Community Social Responsibility Section Head Regional Jasamarga Nusantara Tollroad and implementers. Meanwhile, the recipients of the Corporate Social Responsibility program were 10 respondents from partnerships in the trade, industry and animal husbandry sectors and 4 respondents from community development for religious, educational, and public facilities. The results of this study are the objectives to be achieved in the implementation of the partnership and community development program that have been running. In the community development program, the distribution of this assistance is very effective and efficient. However, the partnership program is still less effective and efficient due to the lack of socialization of the PKBL to the community so that there are still many people who do not know about the program and there are still many constraint factors in terms of loan repayment..